Book Reviews: Volume 24, Number 1 - Grossman, Neal; Hafiz, David Schaffer; Cardena, Etzel; Alvarado, Carlos S.; Tucker, Jim B.; Levin, Michael; McDaniel, Stan V. (Journal of Scientific Exploration, 2010)
The End of Materialism: How Evidence of the Paranormal Is Bringing Science and Spirit Together by Charles T. Tart. Philosophy of Personal Identity and Multiple Personality by Logi Gunnarsson. Eusapia Palladino and Her Phenomena by Hereward Carrington. Can the Mind Survive beyond Death? In Pursuit of Scientific Evidence by Satwant K. Pasricha. Morphic Resonance: The Nature of Formative Causation by Rupert Sheldrake. A New Science of Life: The Hypothesis of Formative Causation by Rupert Sheldrake. “Why AI Is a Dangerous Dream,” Opinion, Interview with Noel Sharkey by Nic Fleming.